PENERAPAN PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR IPA KELAS VI SD NEGERI 004 TEMBILAHAN KOTA KECATAMATAN TEMBILAHAN - Sarminah Sarminah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
The background of this research is the low of science learning result of grade 6 students of SDN 004 TembilahanKota. The purpose of this study is to improve the learning outcomes of science students of grade VI SDN 004Tembilahan Kota with the application of contextual approach. This research was conducted in class VI SDN004 Tembilahan Kota. This research is a Classroom Action Research with two cycles. The subjects of thisresearch are the sixth grade students of SDN 004 Tembilahan Kota lesson year which consist of 30 people with16 men and 14 women. Based on the results of the research from the teacher activity sheets appear to increase ateach meeting. At the first meeting of cycle I 64.3%, the second meeting of cycle I was 67.86%. At the firstmeeting of cycle II 71,43%, and second meeting of cycle II 78,57%. While the student activity also increasesevery meeting. At the first meeting of cycle I 67,86%, second meeting of cycle I 71,43%. At the first meeting ofthe second cycle of 75%, and the second meeting II cycle 78.57%. The learning outcomes in the first cycleincreased by 12.8% from the base score of 67.83% to 76.5%. In the second cycle increased by 17.2% to 79.5%.